The Influence of Osteoporosis and Diabetes on Dental Implant Stability: A Pilot Study - Liliana Sachelarie; Ioana Scrobota; Felicia Cioara; Timea Claudia Ghitea; Corina Laura Stefanescu; Liana Todor; Georgiana Ioana Potra Cicalau (Medicina)
Background and Objectives: Dental implants are a reliable solution for tooth loss; however, systemic conditions like osteoporosis and diabetes, which affect bone quality, healing, and stability, underline the importance of understanding their impact on enhanced outcomes. This study evaluated the comparative effects of osteoporosis and diabetes on dental implant stability over 12 months, utilizing objective implant mobility and stability measures. Materials and Methods: This prospective cohort study involved 50 patients, divided into 21 with type 2 diabetes and 29 with osteoporosis, with implant stability assessed at 6 and 12 months using Osstell ISQ and Periotest M devices and statistical analysis identifying differences between groups and time intervals at a significance level of p < 0.05. Results: At 6 months, the osteoporosis group showed higher initial stability (mean ISQ: 67.04 ± 5.42) compared to the diabetes group (mean ISQ: 62.10 ± 5.46; p = 0.0215)), and by 12 months, both groups showed significant improvements in ISQ scores (osteoporosis: 68.93 ± 4.83; diabetes: 65.79 ± 3.87), with Periotest values indicating more significant reductions in implant mobility, particularly in diabetic patients (osteoporosis: −3.34 ± 1.59; diabetes: −2.81 ± 1.44; p = 0.0001). Conclusions: Osteoporosis and diabetes significantly impact implant stability through distinct osseointegration pathways, emphasizing the need for personalized treatment plans to improve patient outcomes.